ANISOTROPY ANALYSIS OF ULTRASONIC TOMOGRAPHY CORE ROCK ON SEISMIC LOG IN SADEWA FIELD OF KUTEI BASIN, EAST KALIMANTAN - Rizkya Yulianti, Ira
The Kutai Basin is the second-largest and deepest hydrocarbon-rich basin in Indonesia. In the Kutai Basin there is Sadewa Field which is used as research. Sadewa Field is located on the upper slope is one of the fields that will be developed, which requires good seismic modelling and interpretation. Good modelling and interpretation require knowledge of the anisotropic effect, as well as its relationship to the physical and elastic properties of source and reservoir rocks. Ultrasonic tomography is a diagnostic imaging method that uses high-frequency ultrasonic waves. Ultrasonic tomography measurements can measure small structures so that it can provide more precise results regarding the anisotropy parameters and elastic properties of rocks. This study uses ultrasonic tomography measurement data, 3D PSTM seismic data, well data, petrographic data, and physical properties data from laboratory measurement of SDW-4 well core samples. Ultrasonic tomography measurements used 14 rock core samples of SDW-4 at a depth of 10645.5 – 10801.5 ft. The results of processing data found that there were 2 groups in the rock core sample of SDW- 4, namely the economic pay group and the non-economic pay group. The economic pay group tends to have a low AI value, this indicates that the zone contains hydrocarbons. Based on the relationship of anisotropy parameters (?, ?, ?, and ? ) to the AI value, the economic pay group has a high % quartz (> 35%) and low % matrix (< 45%).